Novel Virophages Discovered in a Freshwater Lake in China - Gong, Chaowen; Zhang, Weijia; Zhou, Xuewen; Wang, Hongming; Sun, Guowei; Xiao, Jinzhou; Pan, Yingjie; Yan, Shuling; Wang, Yongjie (Frontiers in Microbiology, 2016)
Virophages are small double-stranded DNA viruses that are parasites of giant DNA viruses that infect unicellular eukaryotes. Here we identify a novel group of virophages, named Dishui Lake virophages (DSLVs) that were discovered in Dishui Lake (DSL): an artificial freshwater lake in Shanghai, China. Based on PCR and metagenomic analysis, the complete genome of DSLV1 was found to be circular and 28,788 base pairs in length, with a G+C content 43.2%, and 28 predicted open reading frames (ORFs). Fifteen of the DSLV1 ORFs have sequence similarity to known virophages. Two DSLV1 ORFs exhibited sequence similarity to that of prasinoviruses (Phycodnaviridae) and chloroviruses (Phycodnaviridae), respectively, suggesting horizontal gene transfer occurred between these large algal DNA viruses and DSLV1. 46 other virophages-related contigs were also obtained, including six homologous major capsid protein (MCP) gene. Phylogenetic analysis of these MCPs showed that DSLVs are closely related to OLV (Organic Lake virophage) and YSLVs (Yellowstone Lake virophages), especially to YSLV3, except for YSLV7. These results indicate that freshwater ecotopes are the hotbed for discovering novel virophages as well as understanding their diversity and properties.